Water security and climate resilience in the Somali Region, Ethiopia: an assessment of the vulnerabilities of refugee and host communities - Singh, Radhika; Mekuria, Wolde; Dessalegn, Mengistu; Melaku, Dagmawi; Adam-Bradford, A.; Ruckstuhl, Sandra (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
Refugee and hosting communities of the Somali Region of Ethiopia are deeply impacted by water insecurity. Water supply and irrigation systems developed by UNHCR and other humanitarian organizations suffer from weak value chains, high running costs, and overburdened infrastructure/equipment, hence are unable to respond to the needs of growing populations. This has led to insecure livelihoods and over-dependence on humanitarian aid. This report aims to identify priority areas to improve water security, as both water supply and irrigation systems are vulnerable to the effects of droughts, floods, and other weather extremes. It recommends prioritizing anticipatory action, enhancing adaptation to climate change, and increasing resilience to economic stresses to strengthen the resilience of water supply and irrigation systems. Anticipatory actions, including identifying locations for water harvesting, upgrading and protecting key infrastructure, and raising community trust in climate forecasts, can minimize the effects of disasters and protect developmental gains. Adaptation to climate change can be enhanced with the identification of new clean water sources and the development of innovative water utility models. Finally, resilience to economic stresses can be mitigated by strengthening value chains, encouraging innovation systems around solar power, and filling water system gaps with local enterprises.